2017
DOI: 10.1253/circj.cj-16-0998
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Clinical Outcome of Asymptomatic vs. Symptomatic Severe Aortic Stenosis After Aortic Valve Replacement

Abstract: Background: There is discordance regarding the effect of symptom status before aortic valve replacement (AVR) on long-term outcome after AVR in severe aortic stenosis (AS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…In the CURRENT AS registry,8 severe HF was the initial symptom during follow-up in a substantial proportion of patients in the conservative group, in whom AVR was less frequently performed than in patients without severe HF, and mortality was extremely high if AVR was not performed. Third, SAVR after symptom development might be carrying higher operative risk than SAVR during the asymptomatic phase 33. Fourth, the annual rate of sudden death during the asymptomatic phase might be higher (1.4%/year) than the rate (<1.0%/year) reported previously 10 13–15.…”
Section: Management Of Asymptomatic Patients With Severe Asmentioning
confidence: 87%
“…In the CURRENT AS registry,8 severe HF was the initial symptom during follow-up in a substantial proportion of patients in the conservative group, in whom AVR was less frequently performed than in patients without severe HF, and mortality was extremely high if AVR was not performed. Third, SAVR after symptom development might be carrying higher operative risk than SAVR during the asymptomatic phase 33. Fourth, the annual rate of sudden death during the asymptomatic phase might be higher (1.4%/year) than the rate (<1.0%/year) reported previously 10 13–15.…”
Section: Management Of Asymptomatic Patients With Severe Asmentioning
confidence: 87%
“…One of the reasons for the poor prognosis of symptomatic patients might be related to greater AS severity and more depressed left ventricular function in symptomatic patients. Indeed, we have recently reported that the long-term outcomes of symptomatic patients with severe AS were worse than those of asymptomatic patients when managed with initial AVR strategy 16 . Therefore, the watchful waiting strategy might be associated with poorer prognosis than early AVR strategy, even if elective AVR could be performed after watchful waiting.…”
Section: Discussionmentioning
confidence: 99%
“…It is typically accepted from the current guidelines that the symptom development is a vital indication for intervention, whether surgical or transcatheter. A recent comprehensive study using the Japanese population recommended early intervention in selected asymptomatic subjects with AS because long-term outcomes of symptomatic patients were worse than those of asymptomatic patients 19. In fact, some groups of patients with AS processed the decompensation without any complaints at daily practice because of frailty, cognitive disorder or workload avoidance.…”
Section: Discussionmentioning
confidence: 99%